Outcome and Treatment of Hepatic Epithelioid Hemangioendotheliomas in Child: A Rare Case Report - Setyoboedi, Bagus; Prihaningtyas, Rendi Aji; Arief, Sjamsul (Journal of Community Medicine and Public Health Research, 2025)
Hepatic tumors in children are relatively rare, accounting for 0.5- 2% of all childhood tumors. Hepatic epithelioid haemangioendothelioma (HEH) is a rare vascular tumour. HEH may appear clinically with nonspecific abdominal symptoms. A 9- year-9-month-old boy presented to the paediatric outpatient clinic with sudden right upper abdominal pain, weight loss, loss of appetite, and weakness. Initial physical examination revealed hepatomegaly. Laboratory tests showed anemia and thrombocytopenia. Meanwhile, liver function tests, serum bilirubin, and serum alpha-fetoprotein (AFP) were within normal limits. Abdominal ultrasound showed hepatomegaly with multiple liver nodules involving both lobes, with a maximum diameter of 4.3 cm and hypoechoic lesions. An MSCT scan of the abdomen revealed numerous solid lesions, and the largest of which measured approximately 3 x 4 x 3.5 cm. These lesions were spread across both lobes and appeared hypodense. These findings are consistent with the hypothesis that HEH of the liver originates from both lobes. Supportive therapy with packed red cell transfusion and supplemental oxygen was started. Steroid therapy using prednisolone orally was started. The patient was following up after 2 weeks of treatment and revealed improvement in clinical condition and laboratory. Hepatic epithelioid hemangioendothelioma should be considered when round, multifocal lesions infiltrating the liver are present, and confirmed by a physician and radiologist. Long-term outcomes are uncertain; therefore, early detection, therapy, and appropriate follow-up are needed.